Dorsal telencephalon-specific Nprl2- and Nprl3-knockout mice: novel mouse models for GATORopathy. Issue 9 (20th November 2021) - Ishida, Saeko; Zhao, Di; Sawada, Yuta; Hiraoka, Yuichi; Mashimo, Tomoji; Tanaka, Kohichi
Abstract: The most frequent genetic cause of focal epilepsies is variations in the GAP activity toward RAGs 1 complex genes DEP domain containing 5 ( DEPDC5 ), nitrogen permease regulator 2-like protein ( NPRL2 ) and nitrogen permease regulator 3-like protein ( NPRL3 ). Because these variations are frequent and associated with a broad spectrum of focal epilepsies, a unique pathology categorized as GATORopathy can be conceptualized. Animal models recapitulating the clinical features of patients are essential to decipher GATORopathy. Although several genetically modified animal models recapitulate DEPDC5 -related epilepsy, no models have been reported for NPRL2 - or NPRL3 -related epilepsies. Here, we conditionally deleted Nprl2 and Nprl3 from the dorsal telencephalon in mice [ Emx1 cre/+ ; Nprl2 f/f ( Nprl2 -cKO) and Emx1 cre/+ ; Nprl3 f/f ( Nprl3 -cKO)] and compared their phenotypes with Nprl2 +/ −, Nprl3 +/ − and Emx1 cre/+ ; Depdc5 f/f ( Depdc5 -cKO) mice. Nprl2 -cKO and Nprl3 -cKO mice recapitulated the major abnormal features of patients—spontaneous seizures, and dysmorphic enlarged neuronal cells with increased mechanistic target of rapamycin complex 1 signaling—similar to Depdc5 -cKO mice. Chronic postnatal rapamycin administration dramatically prolonged the survival period and inhibited seizure occurrence but not enlarged neuronal cells in Nprl2 -cKO and Nprl3 -cKO mice. However, the benefit of rapamycin after withdrawal was less durable in Nprl2 - and Nprl3 -cKO mice compared with Depdc5 -cKO mice. Further studies using these conditional knockout mice will be useful for understanding GATORopathy and for the identification of novel therapeutic targets.